Methods of elimination of rails increased damage in the area of weld joints - E. A. Shur; V. M. Fedin; A. I. Borts; Yu. V. Ronzhina; A. I. Fimkin (Вестник Научно-исследовательского института железнодорожного транспорта, 2019)
Rail weld joints from electric-contact welding in stationary and fi eld conditions, as well as those from aluminothermic welding are weak points on tracks that are easily damaged compared with rails outside the weld joints. Currently, these weak points are the defects connected with lack of penetration in the welding area, burns at the points of poor contact of the rail foot with the current-carrying contact tips, or with defects of the weld joint machining after welding, as well as the local hardness reduction in areas affected by heat after welding, and local heat treatment after welding. Elimination of wide areas of reduced hardness at the weld joint points producing saddles, cracks, and chipping, and promoting rails damage next to such joints is a major challenge for increasing the serviceability of weld joints. This study introduces three avenues for elimination of increased damage of rails at weld joints including:• Improvement of technology and equipment for electriccontact welding and local heat treatment after welding in the stationary and fi eld conditions.• Development of technology and equipment for induction welding in the stationary and fi eld conditions.• Development of technology and equipment for differentiated induction tempering of rails preliminary welded in strings 800 m long.